The Estimation of Economic Valuation on Carbon Sequestration of Agroforestry Land System: Estimasi Nilai Ekonomi Serapan Karbon pada sistem agroforestri di KPH Bogor - Siagian, Kristi; Karuniasa, Mahawan; Mizuno, Kosuke (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
The role of Perhutani and local farmers in developing agroforestry in Bogor Forest Management Unit (FMU) is important for carbon sequestration-based climate mitigation efforts. Different compositions of the plants in seven agroforestry systems in four part of Bogor FMU. Farmers adjust the multipurpose crops planted with Perhutani main plants, which are more dominant. The potential mean annual carbon increment based on aboveground carbon stock of agroforestry is between 2.26 to 66.65 tonnes per hectare, while in 2 monocultures land system is between 13.65 to 18.29 tonnes per hectare. The carbon increment in agroforestry systems is better than monoculture because of plant diversity and different ages. Then, carbon revenue using carbon pricing set by the World Bank-FCPF Program in East Kalimantan is in the range of IDR 1,547,325 to IDR 49,292,405 per hectare, using the Social Cost scheme in the range IDR 12,997,535 to IDR414,056,204 per hectare and using domestic carbon tax is range IDR 635.017 to IDR 20,229,441 perhectare. Regarding carbon revenues, the wider the agroforestry land managed by farmers, the higher the carbon income received. Using the benefit transfer method over a 20-year mitigation period, an estimated 2.19 times increase in carbon revenues is obtained at an inflation rate of 4%.